2008
DOI: 10.1007/s11832-008-0134-9
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary management of clubfeet using the Ponseti method in a district general hospital setting

Abstract: Early results suggest that a combined consultant/physiotherapist-delivered Ponseti service can be effectively and successfully administered in a district general hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
2
24
1
Order By: Relevance
“…There were more patients in group C (unfavorable LTiC angle and favorable ADF angle) than in group B (favorable LTiC angle and unfavorable ADF angle) in our investigation, and it should be pointed out that the decision based on the LTiC angle tended to compel patients to undergo percutaneous Achilles tenotomy. However, percutaneous Achilles tenotomy is also performed in many patients with a favorable ADF angle who show pseudocorrection in the midfoot 9,11 , and the percutaneous Achilles tenotomy rate in the present study was not higher than that in previous studies 5, [19][20][21] . We believe that the use of the LTiC angle as a determinant of the need for percutaneous Achilles tenotomy does not compel patients who do not actually need the procedure to undergo it but helps to obtain a more exact assessment of ankle motion.…”
contrasting
confidence: 61%
“…There were more patients in group C (unfavorable LTiC angle and favorable ADF angle) than in group B (favorable LTiC angle and unfavorable ADF angle) in our investigation, and it should be pointed out that the decision based on the LTiC angle tended to compel patients to undergo percutaneous Achilles tenotomy. However, percutaneous Achilles tenotomy is also performed in many patients with a favorable ADF angle who show pseudocorrection in the midfoot 9,11 , and the percutaneous Achilles tenotomy rate in the present study was not higher than that in previous studies 5, [19][20][21] . We believe that the use of the LTiC angle as a determinant of the need for percutaneous Achilles tenotomy does not compel patients who do not actually need the procedure to undergo it but helps to obtain a more exact assessment of ankle motion.…”
contrasting
confidence: 61%
“…Treatment of clubfoot remains controversial issue regarding the appropriate method to be used (Kampa et al, 2008). Service providers have different perceptions on management of clubfoot.…”
Section: Challenges With Management Approachesmentioning
confidence: 99%
“…Rehabilitation professionals such as physiotherapists are crucial members of the clubfoot management team both in developed and developing countries (Kampa et al, 2008;Shack & Eastwood, 2006). Physiotherapists manage the clubfoot deformity, teach parents/caregivers about clubfoot, the treatment process and the expected outcome (Ireland, 2003).…”
mentioning
confidence: 99%
“…However the Ponseti method has been extended to other healthcare professionals which has already been trialled successfully in the UK within two separate secondary care settings. 39,40 Kampa, et al, 40 used a multidisciplinary team comprising of junior doctors, physiotherapists, nurses and plaster technicians or orthotists. They concluded that the combined approach of a multidisciplinary team and a surgeon when necessary was a success.…”
Section: Non Surgical Interventions For Itevmentioning
confidence: 99%
“…As parent education is key to the treatment's success, having podiatrists available close to home for mid week visits to respond to problems when they arise is likely to reduce the long waiting times in out patients departments which is already a problem cited by both Docker, et al, 39 and Kampa, et al, 40 Docker, et al, also suggested that the earlier intervention of the multidisciplinary team reduced the number of tenotomies required, again cutting the overall healthcare costs.…”
Section: Mcgroggan Dunlopmentioning
confidence: 99%